2018
DOI: 10.1590/1518-8345.1062.2991
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and validation of the Condom Self-Efficacy Scale: application to Brazilian adolescents and young adults

Abstract: Objective:translate and adapt the Condom Self-Efficacy Scale to Portuguese in the Brazilian context. The scale originated in the United States and measures self-efficacy in condom use. Method:methodological study in two phases: translation, cross-cultural adaptation and verification of psychometric properties. The translation and adaptation process involved four translators, one mediator of the synthesis and five health professionals. The content validity was verified using the Content Validation Index, based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…However, the results from this study also confirm findings from other studies, which state that having comprehensive knowledge, for example, on male condom use, does not facilitate translating expressed self-efficacy into action in relation to risky sexual behavior [27,28]. For example, many young people who had expressed self-efficacy and failed to use condoms cited emotional impulsivity or being in the "heat of a moment" and partner refusal or failure to communicate to the partner as reasons why they failed to use condoms.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the results from this study also confirm findings from other studies, which state that having comprehensive knowledge, for example, on male condom use, does not facilitate translating expressed self-efficacy into action in relation to risky sexual behavior [27,28]. For example, many young people who had expressed self-efficacy and failed to use condoms cited emotional impulsivity or being in the "heat of a moment" and partner refusal or failure to communicate to the partner as reasons why they failed to use condoms.…”
Section: Discussionsupporting
confidence: 81%
“…Some of the literature has suggested that early sexual debut is largely a result of poor self-efficacy to negotiate refusal sex [21], which can be in the form of delayed sex [22] or sexual abstinence [23,24]. Low self-efficacy may lead to low or non-condom use [25][26][27][28] or non-use of contraception [29,30]. In Ethiopia, a study conducted among preparatory school students in Sodo Town, Southern Ethiopia, indicates that good selfefficacy was associated with condom use [19].…”
Section: Introductionmentioning
confidence: 99%
“…Access to condom use is one of the strategies to eliminate STIs [ 2 ]. However, in addition to using the family health strategy, teams should assess the effectiveness of condom use in order to work on collective and individual interventions aimed at the population’s needs [ 29 , 30 ]. It is important that health professionals also advise people on the actions to be taken in case of condom breakage during sexual intercourse to minimize the damage related to a possible infection [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%